Peranan Advokat Dalam Menerapkan Mediasi Penal Sebagai Alternatif Penyelesaian Tindak Pidana (Studi Penerapan Mediasi Penal Oleh Advokat Lembaga Bantuan Hukum Tuah Negeri Nusantara Di Kota Pekanbaru) - Nadya Khairunissa; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Penal mediation is an alternative solution to criminal cases outside the court. In the settlement of criminal cases if taking a line of reasoning, there is always a criminal conviction by the judge against the perpetrator, this is philosophically sometimes not satisfying all parties, therefore it is necessary to have a criminal case resolution through ADR (Alternative Dispute Resolution) with the intention can resolve conflicts that occur between perpetrators and victims.This research can be classified in sociological legal research, namely the effort to approach the problem under study with the nature of the law that is real or in accordance with the reality that lives in society. This research is seen from the nature of description, namely a study that illustrates clearly and in detail the review of the role of advocates in applying reason mediation as an alternative to criminal dispute resolution by limiting the discussion and analysis of two aspects, namely the role of advocates, and the legal consequences of the peace agreement from the results of the reasoning mediation.From the results of the problem research there are three main things that can be concluded. First, the Role of Advocates in Applying Penal Mediation to Completion of Criminal Cases Outside the Court is an advocate acting as a third party who is impartial and seeks to find solutions and provide solutions to the disputing parties but the solutions provided are not binding the parties to the dispute, the success of mediation remains dependent on the parties who want peace as a solution outside the court. Second, the legal strength of the peace agreement produced by the mediation of the process of handling criminal cases in the peace agreement produced by reasoning mediation will be legally enforceable for the parties (perpetrators and victims) based on the principle of pacta sunt servanda that the agreement is a law for the maker so obeyed. But the peace agreement is actually not binding on investigators or creates an obligation for investigators to stop the investigation. Even though an act of accountability is desired by the victim, the perpetrator can still be prosecuted until the judge is sentenced.The author's advice, First, should the Central Government and the Regional Government conduct legal development management on the importance of resolving legal issues through the reasoning mediation path. Second, a policy from the government is needed that supports penal mediation through legal institutions by harmonizing the criminal justice system. Third, conducting reasoning mediation needs to be supervised by an advocate organization so that penal mediation is truly implemented because of reasons for the benefit of the parties.Keywords: Role - Penal Mediation - LBH Tuah Negeri Nusantara